Positioning of Ukrainian enterprises on external markets of grain - Пальонка, О. Ю. (Scientific Progress & Innovations, 2017)
The article deals with the essence of positioning, factors and strategies of enterprises positioning. It is determined that today the positioning is the marketing strategy of the enterprise, the essence of which lies in the place occupied by the enterprise in the consciousness of the target audience. The approach to formation and realization of strategies of positioning of agrarian enterprises is highlighted. The main factors that determine the increase of positions in the world ranking of Ukrainian enterprises are described. An example of an effective positioning of Ukrainian enterprises on foreign grain markets is provided with the help of modern logistics infrastructure, product quality, and established trade relations.